Caracterización bioagronómica de cuatro híbridos de pimieinto (Capsicum annun L.) en el cantón Mocache. - Coque Santana, Luis Jonathan (2015)
This research was conducted in the province of Los Rios Region Mocache, the field phase had a duration of three months. block design was completely randomized (DBCA) with four treatments and three repetitions, to establish statistical differences between treatments Tukey test was performed at 95% statistical probability, regarding phytosanitary issues presented in the study were minimum, behaving as resistant to fungal problems such Damping off and the presence of pests as tracers was minimal in Cortez, Oregon, Chrome, Zapata hybrids, the results show that most plant height recorded by the hybrid 30 days treatment 4 obtained hybrid Zapata reached 20.72 cm compared to the hybrid treatment Oregon 3 which had the lowest with 15.65 cm height, treatment 4 consists of the hybrid Zapata was registered the highest number of flowers with a total of 13.39, a difference of treatment 2 composed of chromium hybrid had the lowest number of foliar incidence with 10.50, the greater weight of fruit per plant presented the hybrid treatment 1 Cortez reached a weight of 202.11 g. unlike hybrid treatment 2 Chrome which recorded the lowest weight with 141.35 g, treatment 4 consists of the hybrid Zapata scored the best performance with 34.36 kg per plot unlike hybrid chrome treatment 2 had the lowest performance with 24.89 kg The higher yield per hectare was obtained by treatment 1 comprising hybrid Cortez 15050.80 kg while treatment Chrome 2 hybrid had the lowest performance 11308.52 kg, the best cost-benefit ratio was Zapata treatment with 0.46, describing that for every dollar spent 46 cents of profit is obtained,